The Influence of Time Budget Pressure, Time Deadline Pressure and Work Stress on Audit Quality of External Auditor - Dodik Juliardi Iksan (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
The purpose of this study was to try the goods of time pressure, deadline pressure, and work pressure on test quality among PAF observers in Malang City. The logical model exercised is a multitudinous retrogression dissection where the dependent variables are time pressure( X1), deadline pressure( X2), job pressure( X3) and the independent variable is test quality( Y). The study population was his PAF accountants in Malang, totaling 86. The sample exercised comported of her 52 repliers, utilizing a accessible sample of his eight account enterprises( PAF) in Malang megacity. A Likert scale( 1- 4) questionnaire is exercised for the dimension. Data source is primary. This study shows that time pressure, deadline pressure, and job pressure don't affect the quality of foreign checkups. terminations of this study are that the questionnaire effects don't give his 100 valid comebacks due to lack of management, that the repliers are pacified by youthful observers, and that the study effects are in this range. Secondly, it can not be generalized to multitudinous regions in Indonesia. Research will be limited to a defined bone in Malang City.